PENGARUH PENGGUNAAN METODE BERMAIN WORD CARDTERHADAP KEMAMPUAN MEMBACA PERMULAANDALAM MATA PELAJARAN BAHASA INDONESIAPADA SISWA KELAS II SD MUHAMMADIYAH IDI TELLO BARU - ulfa; Munirah; Khadijah Razak, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of the Word Card Playing Method is one way to solve problems in learning. This study aims to determine the effect of using the word card playing method on the ability to read early in the Indonesian language subject in grade II students of SD Muhammadiyah IDI Tello Baru. This study uses a Pre-experimental research type. The population in this study were grade II students of SD Muhammadiyah IDI Tello Baru consisting of 22 students. The data collection technique used in this study was a pretest and posttest in the form of a reading test. The data analysis technique used in this study is a descriptive data analysis technique and an inferential technique which includes a normality test, a homogeneity test and a hypothesis test. Based on the results of the study, it shows that the average pretest score is 59.32 while the average posttest score is 77.73. The paired sample T-test test shows a significant value (2- Tailed) = 0.000 <0.05. Based on the results obtained, H0 is rejected and H1 is accepted. From the results of the study, it can be concluded that the use of the word card playing method has an effect on the ability to read early in students at SD Muhammadiyah IDI Tello Baru.